The Relationship Between Community Characteristics and Urban Sprawl in Driyorejo Sub-District, Gresik Regency, Indonesia - Pahlevi, Muhammad Reza; Dinanti, Dian; Subagiyo, Aris; Qomariyah, Yuyun; Varo, Joeli (Perencanaan Wilayah dan Kota FT UB, 2023)
The Driyorejo sub-district is a buffer zone for the city of Surabaya due to limited land for the development of residential areas. Many areas are built up due to the influence of the city of Surabaya and that can be called urban sprawl. Urban sprawl is a phenomenon of urban expansion marked by a city’s size increase due to population growth and a rapid urbanization rate, or the movement of people from rural to urban areas. A level of urban sprawl with a high one can be found in the Driyorejo Sub-District, one of the sub-districts in the southern Gresik Regency. This study uses a quantitative method that is analyzed using correlation analysis to determine the relationship that occurs between urban sprawl and the characteristics of the community in the study area. According to the study's findings, three villages have low levels of urban sprawl, four have medium levels, and four have high levels. The relationship between the typology's findings and the neighborhood's social makeup—including its level of education, economic situation, the welfare of its families, and the cost of land—will then be apparent. People with pre-prosperous family status frequently reside in villages with a tall typology of urban sprawl because of the strong correlation between urban sprawl and the Pra Prosperous family. Additionally, those in the agricultural industry are closely related to urban sprawl. Theoretically, people working in agriculture are more likely to select the same location for their primary residence and employment.